THE MEANING OF A LEGAL CATEGORY OF “SANCTION” - A. S. Panova (Russian Journal of Economics and Law)
Objective: to study the legal category of sanction. Methods: dialectical, systematic, and logical methods of analysis, synthesis. Results: the study of the legal category of "sanction" has shown that a sanction can be applied on a regulatory or contractual basis (if stipulated by a civil agreement), and as the measures of liability and protection. One of the promising directions of its use is the motivating one - sanctions can provide the legal consequences favorable for those who observe the behavior stipulated by the law. The following is offered as the direction of development of domestic legislation on sanctions: verification of compliance of the sanctions amount and terms with the offences gravity; introduction of previously non-existent sanctions (for example, speculation on food and currency markets); the use of discretionary sanctions as a means of positive legal stimulation of the economy. Scientific novelty: the conclusion is made about the nature of the sanctions; it is proved that the sanction is a legal means, the use of which enables the victim to protect their violated (challenged) rights provided for by the legislation and (or) the agreement, and implies adverse consequences of property and (or) organizational nature for the offender. The sanctions application has its own peculiarities. Their use is aimed at curbing the illegal actions of the offender (debtor), to stimulate them to the proper performance of statutory or contractual duties; often sanctions are aimed at compensating for damage caused to the creditor. A peculiar feature of the sanctions is that they are a necessary component of the legal system. Practical value: the results obtained can be used to conduct economic and legal research relating to the economics and entrepreneurship, in treaty practice, in teaching the disciplines of Civil Law, Business Law, Commercial Law, etc.